2021
DOI: 10.3389/fpsyg.2021.725199
|View full text |Cite
|
Sign up to set email alerts
|

How CEO Workaholism Influences Firm Performance: The Roles of Collective Organizational Engagement and TMT Power Distance

Abstract: Based on upper echelons theory, the current study examines how and under what conditions CEO workaholism influences firm performance. Specifically, we propose that CEO workaholism is positively related to collective organizational engagement, which has a subsequent positive effect on firm performance. Top management team (TMT) power distance would moderate the relationship between CEO workaholism and collective organizational engagement in such a way that workaholic CEOs are more likely to stimulate collective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Extant research has successfully indicated various internal and external factors affecting changes in the patent strategy, among which TMT is viewed as one of the key elements (Wang, 2016 ; Zhao et al, 2020 ; She et al, 2021 ). Including CEO, board of directors, independent directors, and top managers, TMT members are faced with both opportunities and challenges due to rapid changes in the industrial and economic context of enterprises.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Extant research has successfully indicated various internal and external factors affecting changes in the patent strategy, among which TMT is viewed as one of the key elements (Wang, 2016 ; Zhao et al, 2020 ; She et al, 2021 ). Including CEO, board of directors, independent directors, and top managers, TMT members are faced with both opportunities and challenges due to rapid changes in the industrial and economic context of enterprises.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Consequently, their values and assumptions gradually become embedded within the organizational climate (Jaiswal and Dhar, 2015). This climate has been demonstrated to be instrumental in directing and coordinating employees’ efforts toward achieving organizational goals (Hur et al , 2023; She et al , 2021). Accordingly, our paper examines the mediation of ethical, service and initiative climates in CEO responsible leadership’s association with organizational outcomes (CSR and organization performance).…”
Section: Theory and Hypothesis Developmentmentioning
confidence: 99%
“…Unfavourable work characteristics may also affect the QWL and performance adversely. With varied poor job resources at employees' disposal (She et al, 2021), workaholic individuals are unable to reduce the potentially negative effect of the high job demands experienced (Akinwale and George, 2020). Also, workaholics have few chances to recuperate and mend adequately from their work sufficiently and this largely affects their QWL (Akinwale and George, 2023).…”
Section: Workaholism and Quality Of Work-lifementioning
confidence: 99%